Effect of Menstruation on Speed, Strength and Selected Physiological Variables: Exploring the Impact of Menstruation on Speed, Strength, and Physiological Variables (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The speed and the accuracy of a perceptual judgmentdepend on the strength of the sensory stimulation. When stimulus strength ishigh, accuracy is high and response time is fast; when stimulus strength islow, accuracy is low and response time is slow. Although the psychometricfunction is well established as a tool for analyzing the relationship betweenaccuracy and stimulus strength, the corresponding chronometric function for therelationship between response time and stimulus strength has not received asmuch consideration.